A Novel Pentadentate Redox-Active Ligand and Its Iron(III) Complexes: Electronic Structures and O2 Reactivity - Metzinger, Ramona; Demeshko, Serhiy; Limberg, Christian (Chemistry : a European journal, 2014)
A novel redox‐active ligand, H4Ph2SLAP (1) which was designed to be potentially pentadentate with an O,N,S,N,O donor set is described. Treatment of 1 with two equivalents of potassium hydride gave access to octametallic precursor complex [H2Ph2SLAPK2(thf)]4 (2), which reacted with FeCl3 to yield iron(III) complex [H2Ph2SLAPFeCl] (3). Employing Fe[N(SiMe3)2]3 for a direct reaction with 1 led to ligand rearrangement through CS bond cleavage and thiolate formation, finally yielding [HLAPFe] (5). Upon exposure to O2, 3 and 5 are oxidized through formal hydrogen‐atom ion from the ligand NH units to form [Ph2SLSQFeCl] (4) and [LSQFe] (6) featuring two or one coordinated iminosemiquinone moieties, respectively. Mössbauer measurements demonstrated that the iron centers remain in their +III oxidation states. Compounds 3 and 5 were tested with respect to their potential as models for the catechol dioxygenase. Thus, they were treated with 3,5‐di‐tert‐butyl‐catechol, triethylamine and O2. It turned out that the iron–catecholate complexes react with O2 in dichloromethane at ambient conditions through CC bond cleavage mainly forming extradiol cleavage products. Intradiol products are only side products and quinone formation becomes negligible. This observation has been rationalized by a dissociation of two donor functions upon coordination of the catecholate. A radical convention: A novel pentadentate O,N,S,N,O ligand system, LH4, which is redox active, has been developed, so that its iron(III) complex (H2LFeCl) reacts with O2. H atoms are ed from the NH units present so that the ligand is converted into a diradical, featuring two iminosemiquinonato moieties that clamp a high‐spin iron(III) center. The complex proved capable of mimicking catechol dioxygenase reactivity, and mediates extradiol cleavage with remarkable selectivity.